Oestrogen-deficient female aromatase knockout (ArKO) mice exhibit depressive-like symptomatology. - Dalla, C; Antoniou, K; Papadopoulou-Daifoti, Z.; Balthazart, J; Bakker, J (Eur J Neurosci, 2004)
We recently found that female aromatase knockout (ArKO) mice that are deficient in oestradiol due to a targeted mutation in the aromatase gene show deficits in sexual behaviour that cannot be corrected by adult treatment with oestrogens. We determined here whether these impairments are associated with changes in general levels of activity, anxiety or 'depressive-like' symptomatology due to chronic oestrogen deficiency. We also compared the neurochemical profile of ArKO and wild-type (WT) females, as oestrogens have been shown to modulate dopaminergic, serotonergic and noradrenergic brain activities. ArKO females did not differ from WT in spontaneous motor activity, exploration or anxiety. These findings are in line with the absence of major neurochemical alterations in hypothalamus, prefrontal cortex or striatum, which are involved in the expression of these behaviours. By contrast, ArKO females displayed decreased active behaviours, such as struggling and swimming, and increased passive behaviours, such as floating, in repeated sessions of the forced swim test, indicating that these females exhibit 'depressive-like' symptoms. Adult treatment with oestradiol did not reverse the behavioural deficits observed in the forced swim test, suggesting that they may be due to the absence of oestradiol during development. Accordingly, an increased serotonergic activity was observed in the hippocampus of ArKO females compared with WT, which was also not reversed by adult oestradiol treatment. The possible organizational role of oestradiol on the hippocampal serotonergic system and the 'depressive-like' profile of ArKO females provide new insights into the pathophysiology of depression and the increased vulnerability of women to depression.
Keywords: Animals; anxiety; Aromatase; Behavior, Animal; Biogenic Monoamines; Brain; Brain Chemistry; Depression; Estradiol; Exploratory Behavior; Female; Homovanillic Acid; Hydroxyindoleacetic Acid; Male; Maze Learning; Mice; Mice, Knockout; Motor Activity; Ovariectomy; Sexual Behavior; Swimming; Time Factors